Analisis Penerapan Peraturan Komisi Pemberantasan Korupsi Nomor 1 Tahun 2021 dalam Kasus Pemberhentian 57 Pegawai KPK yang Tidak Lolos Tes Wawasan Kebangsaan - Tania Putri Anhary (LPPM Universitas Ekasakti Padang, 2023)
Analysis of the Corruption Eradication Commission Regulation Number 1 of 2021 concerning the dismissal of 57 KPK employees who did not pass the National Insight Test violates the Corruption Eradication Commission Regulation No. 1 of 2021, there are 2 reasons underlying this, the first is that the employees were dismissed because they did not pass the National Insight Test alone, even though the President stated that the National Insight Test was not used as a basis for dismissing Corruption Eradication Commission employees. Secondly, the dismissal was carried out by KPK Chairman Firli Bahuri, which should be according to Article 5 in the Corruption Eradication Commission Regulation Number 1 of 2021, the dismissal is carried out by the government, which in this case is President Joko Widodo.Problems related to the dismissal of 57 KPK employees who did not pass the National Insight Test based on the concept of authority regarding resolving all forms of injustice by the ruler to the rights of the people. Because the 57 dismissed employees of the Corruption Eradication Commission felt deprived of the right and opportunity to submit their right of self-defense because during the trial the decision was rejected and there was no consideration from other institutions except only from the results of the National Insight Test.The research was collected using the literature study method (library research). The data collected was then analyzed using descriptive analysis techniques arranged systematically so that it becomes concrete data regarding the analysis of Corruption Eradication Commission Regulation Number 1 of 2021 concerning the dismissal of 57 Corruption Eradication Commission employees who did not pass the National Insight Test.